Visual Impairment Is Associated With Depressive Symptoms—Results From the Nationwide German DEGS1 Study - Alexander K. Schuster; Jonas Tesarz; Jasmin Rezapour; Manfred E. Beutel; Bernd Bertram; Norbert Pfeiffer (Frontiers in Psychiatry, 2018)
IntroductionVisual impairment (VI) is associated with a variety of comorbidities including physical and mental health in industrial countries. Our aim is to examine associations between self-reported impairment and depressive symptoms in the German population.MethodsThe point prevalence of self-reported VI in Germany was computed using data from the German Health Interview and Examination Survey for adults from 2008 to 2011 (N = 7.783, 50.5% female, age range 18–79 years). VI was surveyed by two questions, one for seeing faces at a distance of 4 m and one for reading newspapers. Depressive symptoms were evaluated with the Patient Health Questionnaire-9 questionnaire and 2-week prevalence was computed with weighted data. Depressive symptoms were defined by a value of ≥10. Logistic regression analysis was performed to analyze an association between self-reported VI and depressive symptoms. Multivariable analysis including adjustment for age, gender, socioeconomic status, and chronic diseases were carried out with weighted data.ResultsThe 2-week prevalence of depressive symptoms was 20.8% (95% CI: 16.6–25.7%) for some difficulties in distance vision and 14.4% (95% CI: 7.5–25.9%) for severe difficulties in distance vision, while 17.0% (95% CI: 13.3–21.4%), respectively, 16.7% (95% CI: 10.7–25.1%) for near vision. Analysis revealed that depressive symptoms were associated with self-reported VI for reading, respectively, with low VI for distance vision. Multivariable regression analysis including potential confounders confirmed these findings.ConclusionDepressive symptoms are a frequent finding in subjects with difficulties in distance and near vision with a prevalence of up to 24%. Depressive comorbidity should therefore be evaluated in subjects reporting VI.